2002
DOI: 10.1023/a:1019953914467
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The proximal region of the high-molecular-weight glutenin promoter of the Dx5 gene (PrHMWG-Dx5) carries an atypical bifactorial endosperm box containing two cis-acting elements, namely a G-box like motif followed by a prolamin-box motif (Pb1). Transient expression assays in maize endosperm indicate that a promoter fragment containing at least the G-box like element is necessary and sufficient for maximal expression of the HMWG-Dx5 promoter. In transformed maize, we have shown that a 89 bp sequence bearing the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 47 publications
1
17
0
Order By: Relevance
“…Previous reports demonstrated that the 277 bp immediately upstream of the TSS are sufficient for temporal and tissue-specific regulation (Halford et al, 1989; Norre et al, 2002). There is also strong evidence indicating that mutations in this region are responsible for the silencing of Glu-A1-2 (Halford et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous reports demonstrated that the 277 bp immediately upstream of the TSS are sufficient for temporal and tissue-specific regulation (Halford et al, 1989; Norre et al, 2002). There is also strong evidence indicating that mutations in this region are responsible for the silencing of Glu-A1-2 (Halford et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…We also determined the in vitro binding of SPA to the G-box motif, which was previously shown to bind bZIP proteins (Norre et al, 2002). As shown in Figure 7A, arabinose treatment induced expression of a protein of 50–75 kDa that was not present in uninduced cell extracts.…”
Section: The Glm-gata Box Is Involved In the Regulation Of Glu-b1-1 Ementioning
confidence: 99%
See 3 more Smart Citations